Mechanism of catalytic conversion of kerosene co-refining heavy oil to BTEXN by Py-GC/MS based on "point-line-surface-body" step by step research strategy. (15th January 2023) - Yang, Jiafeng; Yao, Qiuxiang; Liu, Yongqi; Wang, Linyang; Ma, Duo; He, Lei; Gao, Junwen; Zhang, Yujuan; Ma, Li; Sun, Ming; Ma, Xiaoxun
Graphical abstract: Highlights: Model compound (P), mixed compound (L), group component (S), KCR-H (B) were studied. Conversion mechanism of KCR-H to BTEXN based on the P-L-S-B research strategy. Catalytic performance of single metal and bimetallic modified ZSM-5 by Py-GC/MS. Oxygenated compounds tend to have a synergistic effect with aliphatic compounds. Abstract: Kerosene co-refining heavy oil (KCR-H), KCR-H six group components (KCR-HS), six typical model compounds representing the KCR-HS and its mixed model compound were selected as raw materials. The effects of the physicochemical properties of single and bi-metallic modified HZSM-5 (Me/Z-5) on the selectivity and yield of benzene (B), toluene (T), ethylbenzene (E), xylene (X), naphthalene (N) in cracking products were investigated by pyrolysis–gas chromatograph/mass spectrometer (Py-GC/MS). The results show that Ni-Mo/Z-5 exhibits superior selectivity for light aromatic in the catalytic conversion of tetradecane, benzofuran, and KCR-H, compared with Z-5. Additionally, oxygenated and aliphatic compounds are more easily converted to light aromatics than PAHs and nitrogen-containing compounds. Using Ni-Mo/Z-5 catalytic conversion benzofuran, the selectivity of BTEXN in the cracking product is 65.01 %, which is 23.44 times higher than pyrene (2.66 %). Due to the preferential cracking of benzofuran, small molecular fragments prepared by tetradecane and methyl naphthalene promote the catalytic conversion of methyl phenol, quinoline, and pyrene. Compared with the theoretical BTEXN yield (1338.39 mg/kg), the experimental BTEXN yield obtained from mixed model compounds (MCs) increasing by 37.95 %, which is 1846.40 mg/kg. In addition, the BTEXN selectivity of saturates (Satur) over Ni-Mo/Z-5 is 62.97 %, increases by 12.97 % compared with tetradecane, which represents the components of this group, indicating that the synergistic effect between oxygenated compounds and aliphatic compounds is conducive to produce light aromatics. Furthermore, based on the structural characteristics and catalytic properties of metalmodified Z-5 and the conformational relationships between points, lines, surfaces, and bodies, possible catalytic conversion mechanisms and pathways for KCR-H and KCR-HS were proposed.